ANALISA USAHA DAN PEMASARAN EMPING MELINJO DI KECAMATAN MUTIARA KABUPATEN PIDIE - M. Yogi Rofyandi; Amri Amri (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
AbstractThis study aims to determine the business analysis and marketing of melinjo chips in Pidie District, Mutiara District. The analytical method used is descriptive analysis method using primary data, the number of samples used in this method is 40 melinjo chips and 6 melinjo chips. Determination of the Number of Samples using purposive random sampling method. The results showed that the production of emping melinjo for each month can produce an average of 166.5 kg with a daily production of 3.72 kg. The average monthly income for melinjo chips is IDR 6,720,000 or IDR 223,200 evry day, equivalent to IDR 60,000 / kg. While the profits of the craftsmen every month are as much as Rp. 2,507,920, - or IDR. 83,597, -evry day, equivalent to IDR. 22,472 / kg. Marketing margin in Channel B Pattern (Craftsman - Tengkulak / Agent – Trader - consumer) is IDR 15,000 / kg, while in Channel A Pattern (Craftsmen – Traders - consumers) the margin is IDR 10,000/kg. This means Channel A pattern is more efficient than Channel B pattern in melinjo chips marketing. at the research location.Keywords: cost analysis, marketing channel, purposive random sampling